2006
DOI: 10.1158/1078-0432.ccr-06-1178
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-Dependent Synergy between the Heat Shock Protein 90 Inhibitor 17-(Dimethylaminoethylamino)-17-Demethoxygeldanamycin and Doxorubicin Restores Apoptosis to p53-Mutant Lymphoma Cell Lines

Abstract: Purpose: Loss of p53 function impairs apoptosis induced by DNA-damaging agents used for cancer therapy. Here, we examined the effect of the heat shock protein 90 (HSP90) inhibitor 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (DMAG) on doxorubicin-induced apoptosis in lymphoma. We aimed to establish the optimal schedule for administration of both drugs in combination and the molecular basis for their interaction. Experimental Design: Isogenic lymphoblastoid and nonisogenic lymphoma cell lines differing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
5
28
1
Order By: Relevance
“…For that reason, the drugs were used at the same concentration of 200 nM in subsequent experiments. Besides this, the selected drug concentration is consistent with the previously reported 100 nM for 17-DMAG (Robles et al, 2006;Koll et al, 2008).…”
Section: Effects Of Hsp90 Inhibitors On Cell Growth and Radiosensitivitysupporting
confidence: 90%
See 2 more Smart Citations
“…For that reason, the drugs were used at the same concentration of 200 nM in subsequent experiments. Besides this, the selected drug concentration is consistent with the previously reported 100 nM for 17-DMAG (Robles et al, 2006;Koll et al, 2008).…”
Section: Effects Of Hsp90 Inhibitors On Cell Growth and Radiosensitivitysupporting
confidence: 90%
“…The growth inhibition assay was carried out essentially as described elsewhere (Robles et al, 2006). Serial dilutions of Hsp90 inhibitors (0 -5 mM) in CGM were added to cell cultures in duplicates.…”
Section: Growth Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrated that HSP90 inhibitors can sensitize cells to the cytotoxic effects of DNAdamaging agents, including IR, primarily through downregulation of cell survival and cytoprotective factors (Arlander et al, 2003;Bisht et al, 2003;Rahmani et al, 2003;Bull et al, 2004;Dote et al, 2006;Robles et al, 2006). However, GA has also been shown to abrogate G 2 arrest in doxorubicin-treated lymphoma and irradiated carcinoma cells (Bull et al, 2004;Dote et al, 2006;Robles et al, 2006;Sugimoto et al, 2007). Mechanistic studies on the enhancement of IR cytotoxicity by HSP90 inhibition, particularly those focusing on G 2 checkpoint abrogation, are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, this could be due to activation of wild-type p53 and consequent p53-dependent apoptosis. Further research has shown a synergistic effect between 17-DMAG and Doxorubicin, demonstrating a sensitisation of p53 mutated cells to Doxorubicin-induced cell death (Robles et al 2006). …”
Section: Important Hspc1 Client Proteins In Cllmentioning
confidence: 99%